2016
DOI: 10.4236/ojrm.2016.52004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Epidermal Growth Factor-Incorporating Skin Care Product in Culture Experiment Using Human Fibroblasts

Abstract: This study aimed to investigate the potential of a skin care product composed of hyaluronic acid (HA) and collagen (Col) sponge containing epidermal growth factor (EGF), vitamin C derivative (VC), glucosylceramide (GC), poly(γ-glutamic acid) (PGA), and argentine (Arg). High-molecular weight HA aqueous solution, hydrolyzed low-molecular weight HA aqueous solution, and heat-denatured Col aqueous solution were mixed, into which each aqueous solution containing EGF, VC, GC, PGA, or Arg were added, followed by free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…PGA is known to form a soft, smooth, self-elastic and moisturizing film on skin and stimulate natural moisturizing factors, and its 3D molecule structure network allows for high water retention with humectant activity [10,21,[23][24][25][26][27]. In another study, an enhanced human-derived fibroblasts proliferation has been observed after being treated with a skin care sponge, containing poly-(γ-glutamic acid) [28]. PGA esters have been observed to modify collagen gels on human skin fibroblast cell lines HFF-1 and 3T3 [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…PGA is known to form a soft, smooth, self-elastic and moisturizing film on skin and stimulate natural moisturizing factors, and its 3D molecule structure network allows for high water retention with humectant activity [10,21,[23][24][25][26][27]. In another study, an enhanced human-derived fibroblasts proliferation has been observed after being treated with a skin care sponge, containing poly-(γ-glutamic acid) [28]. PGA esters have been observed to modify collagen gels on human skin fibroblast cell lines HFF-1 and 3T3 [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This skin care product is water-soluble, because of no intermolecular cross-linking among HA and Col. This skin care product (5 cm × 8 cm) contains EGF at a concentration of 1.0 µg/cm 2 [45].…”
Section: Skin Care Product Using Growth Factor and Biomaterialsmentioning
confidence: 99%
“…The result demonstrated that fibroblasts in collagen gel sheet released 3.7-times more VEGF (Figure 14) and 25-times more HGF in +EGF group compared with −EGF group (Figure 15). EGF-incorporating skin care product has a potential to stimulate effectively fibroblast to synthesize an increased amount of VEGF and HGF [45].…”
Section: Fundamental Study Using Egf-incorporating Skin Care Productmentioning
confidence: 99%
“…Base on the results related to the skin care product described above, another skin care product was developed [56]. This commercial available skin care product is composed of HA and Col containing EGF and VC, supplemented with GC, PGA, and Arg as cosmetic ingredients (EGF-skin care product).…”
Section: Skin Care Product Composed Of Hyaluronic Acid and Collagen Smentioning
confidence: 99%